Multi-omics profiling and digital image analysis reveal the potential prognostic and immunotherapeutic properties of CD93 in stomach adenocarcinoma - Wu, Baokang; Fu, Lei; Guo, Xingqi; Hu, Huixin; Li, Yang; Shi, Yu; Zhang, Yizhou; Han, Shukun; Lv, Chao; Tian, Yu (Frontiers in Immunology, 2023)
Background: Recent evidence highlights immunotherapy has significantly improved patient outcomes. CD93, as a type I transmembrane glycoprotein, was correlated with tumor-associated angiogenesis; however, how CD93 correlates with immunotherapy in stomach adenocarcinoma (STAD) remains unclear. Methods: TCGA, GTEx, GEO, TIMER2.0, HPA, TISIDB, TCIA, cBioPortal, LinkedOmics, and ImmuCellAI public databases were used to elucidate CD93 in STAD. Visualization and statistical analysis of data were performed by R (Version 4.1.3), GraphPad (Version 8.0.1), and QuPath (Version 0.3.2). Results: CD93 was highly expressed in STAD compared with adjacent normal tissues. Overexpression of CD93 was significantly correlated with poor prognosis in STAD. There was a negative correlation between CD93 expression levels with CD93 mutation and methylation in STAD. Our results revealed that CD93 expression was positively associated with most immunosuppressive genes (including PD-1, PD-L1, CTLA-4, and LAG3), immunostimulatory genes, HLA, chemokine, and chemokine receptor proteins in STAD. Furthermore, in STAD, CD93 was noticeably associated with the abundance of multiple immune cell infiltration levels. Functional HALLMARK and KEGG terms enhancement analysis of CD93 through gene set enrichment analysis (GSEA) was correlated with the process of the angiogenesis pathway. Subsequently, DIA results by QuPath revealed the properties of CD93+ cells were statistically significant in different regions of stomach cancer and normal stomach tissue. Finally, we utilized external databases, including GEO, TISIDB, ImmuCellAI, and TCIA to validate that CD93 plays a key role in immunotherapy of STAD. Conclusion: Our study reveals that CD93 is a potential oncogene and is an indicative biomarker of a worse prognosis, and exerts its immunomodulatory properties and potential possibilities for immunotherapy in STAD.